Formulation Development, Optimization, And Characterization Of Niosomal Nanocarriers For Improved Drug Delivery - B. Ghanmode, Akshay; S. Malthankar, Akash; M. Jawalkar, Gajanan; N. Somnathe, Dnyanesha; S. Phuse, Amruta (Journal of Neonatal Surgery, 2025)
The present investigation was undertaken to perform comprehensive preformulation studies and develop an optimized niosomal drug delivery system for Ticagrelor with the objective of enhancing its delivery performance. Ticagrelor, a white crystalline powder with a melting point of 138 ± 2 °C, exhibited high solubility in organic solvents such as ethanol and methanol, whereas limited solubility was observed in distilled water and phosphate buffer (pH 6.8). Ultraviolet spectroscopic analysis confirmed the identity of the drug, showing maximum absorbance (λ_max) at 255 nm in ethanol and 256.2 nm in phosphate buffer. Fourier transform infrared (FTIR) spectroscopy revealed no significant shifts in characteristic peaks, indicating good compatibility between Ticagrelor and the selected excipients. Niosomal vesicles were formulated using the ether injection technique and systematically optimized employing a 3² full factorial experimental design. Among the developed formulations, the optimized batch (A9) demonstrated superior performance, achieving an entrapment efficiency of 89.7%, a mean particle size of 280.5 nm, and a zeta potential of −26.8 mV, indicative of satisfactory vesicular stability. Scanning electron microscopy (SEM) confirmed the formation of well-defined, spherical vesicles. Differential scanning calorimetry (DSC) and X-ray diffraction (XRD) analyses revealed a reduction in crystallinity of Ticagrelor, suggesting its transformation from a crystalline to an amorphous state upon encapsulation within the niosomes. In-vitro drug release studies demonstrated a sustained release behavior, with cumulative drug release ranging from 20.09% to 91.13%, confirming the controlled release potential of the niosomal system. Ex-vivo permeability studies conducted using a Franz diffusion cell apparatus showed significantly enhanced drug permeation from niosomal formulations compared to the pure drug, indicating improved transmembrane transport. Precompression parameters confirmed acceptable flow properties of the powder blend. Furthermore, evaluation of the compressed niosomal tablets revealed satisfactory mechanical strength, with hardness of 5.2 kg/cm², friability of 0.652%, and drug content uniformity of 90.7%, all of which complied with pharmacopeial specifications. Overall, the optimized Ticagrelor-loaded niosomal formulation demonstrated enhanced stability, controlled drug release, and improved permeability, highlighting its potential as an effective and promising delivery system for improving the bioavailability of Ticagrelor....